Capital Control Measures: A New Dataset - Andrés Fernández; Michael W. Klein; Alessandro Rebucci; Martin Schindler; Martín Uribe (Inter-American Development Bank (IDB), 2015)
This paper presents and describes a new dataset of capital control restrictions on both inflows and outflows of 10 categories of assets for 100 countries over the period 1995 to 2013. Building on the data first presented in Schindler (2009) and other datasets based on the analysis of the IMF's Annual Report on Exchange Arrangements and Exchange Restrictions (AREAER), this dataset includes additional asset categories, more countries, and a longer time period. The paper discusses the manner in which information in the AREAER is translated into a usable dataset. The paper additionally characterizes the data with respect to the prevalence of controls across asset categories, the correlation of controls across asset categories and between controls on inflows and controls on outflows, the aggregation of the separate categories into broader indicators, and the comparison of this dataset with other indicators of capital controls.
hdl:11319/6814
Keywords: C82; F21; F32; F36; F38; F40; 330; Capital flows; Financial integration; Capital control measures